The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/jems.12291
|View full text |Cite
|
Sign up to set email alerts
|

Can social media lead to labor market discrimination? Evidence from a field experiment

Abstract: In this paper, we investigate the role of social media as a source of information for recruiters to discriminate applicants. We set up a field experiment over a 12‐month period, involving more than 800 applications from two fictitious applicants which differed in their perceived origins, which is an information available only from their Facebook profiles. During the experiment, an unexpected change in the Facebook layout reduced the salience of the information available on social media profiles. Before this ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…As for policy implication, one might wonder if a policy prohibiting a photo from CV could help reduce discrimination against appearance. In France, Manant et al (2014) found that despite having no photo on the CV, recruiters did gather information about their fictitious candidates' looks and religious practice from their Facebook profiles.…”
Section: Resultsmentioning
confidence: 99%
“…As for policy implication, one might wonder if a policy prohibiting a photo from CV could help reduce discrimination against appearance. In France, Manant et al (2014) found that despite having no photo on the CV, recruiters did gather information about their fictitious candidates' looks and religious practice from their Facebook profiles.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [1] find no significant discrimination due family structure and sexual orientation, while a negative effect is elicited for radical religious stance. The supposed origin of the user is found to have a significant effect on the number of replies a person gets to a job application [34]. The chances to obtain short-term accommodation online are influenced by the assumed racial origin [14].…”
Section: Related Workmentioning
confidence: 99%
“…Below, we illustrate contexts in which users' lives are influenced by their online activity. The authors of [1] and [34] create fictitious Facebook profiles in which they vary only one type of personal data to assess its influence during job search. The authors of [1] find no significant discrimination due family structure and sexual orientation, while a negative effect is elicited for radical religious stance.…”
Section: Related Workmentioning
confidence: 99%
“…Social media screening of applicants may induce bias (Wade et al 2020) and discrimination (Manant et al 2019) for a variety of reasons. One source of discrimination against applicants is the demographic information published on a social media profile.…”
Section: Bias Suppressionmentioning
confidence: 99%
“…In most social media screening contexts, applicants are unaware that the employer uses social media screening, to what extent information is gathered from social networks, and how strongly it influences hiring decisions (Jeske and Shultz 2016;McDonald and Thompson 2016). Thus, many rejected applicants are never told that an adverse decision was made on the basis of social media screening (Clark and Roberts 2010), and discrimination may occur without the applicant's knowledge (Manant et al 2019). Therefore, the screening of online sources is considered as an "extractive" rather than an "interactive" search for information, as it does not involve two-way communication with the applicant (Berkelaar 2014(Berkelaar , 2017Berkelaar and Buzzanell 2014).…”
Section: Representativenessmentioning
confidence: 99%